Tertiary Amine‐Ethylene Glycol Based Tandem CO2 Capture and Hydrogenation to Methanol: Direct Utilization of Post‐Combustion CO2. Issue 23 (6th November 2020) - Sen, Raktim; Koch, Christopher J.; Goeppert, Alain; Prakash, G. K. Surya
Abstract: Carbon dioxide capture using tertiary amines in ethylene glycol solvent was performed under ambient conditions. Subsequently, the CO2 captured as alkyl carbonate salts was successfully hydrogenated to methanol, in the presence of H2 gas and Ru‐Macho‐BH catalyst. A comprehensive series of tertiary amines were selected for the integrated capture and conversion process. While most of these amines were effective for CO2 capture, tetramethylethylenediamine (TMEDA) and tetramethylbutanediamine (TMBDA) provided the best CH3 OH yields. Deactivation of the base due to side reactions was significantly minimized and substantial base regeneration was observed. The proposed system was also highly efficient for CO2 capture from a gas mixture containing 10 % CO2, as found in flue gases, followed by tandem conversion to CH3 OH. We postulate that such high boiling tertiary amine‐glycol systems as dual capture and hydrogenation solvents are promising for the realization of a sustainable and carbon‐neutral methanol economy in a scalable process. Abstract : Turning flue gas into fuel : CO2 capture from flue gas (10 % CO2 ) is demonstrated and the captured species were directly hydrogenated to methanol, a value‐added carbon feedstock using a ruthenium pincer catalyst. The integrated process comprises stable and high boiling tertiary amines in ethylene glycol solvent, mediating both the capture and conversion steps. This study is key in developing a sustainable and carbon‐neutral economy.